Analytical Model Evaluation on Tin Slag Polymer Concrete Behavior under Compression - Manda, M. S.; M. R. M., Rejab; A.H, Shukur; S.S, Amirnuddin; M.K, Kasmar (2022)
Tin Slag Polymer Concrete (TSPC) is a new material and there was no available analytical model that has been used in describing its behavior. This study has employed a previous analytical model to represent TSPC compressive behavior, especially in the stress-strain relationship of concrete material. Hognestad model, Desayi & Krishnan model, Popovics model and Carreira & Chu model have been considered in this evaluation. The experimental data from the previous researchers are referred to predict the relationship and validated the analytical model computation. Comparison is made by the shape of the stress-strain curve, elastic modulus, yield strength and maximum strength. Carreira & Chu model has been found as the best analytical model that may be employed to describe TSPC behavior under compression. The predicted shape of the stress-strain curve, elastic modulus, yield strength and maximum strength has shown a good match with experimental data and true data. These findings may facilitate future parametric study based on the analytical model with the addition of confining pressure factors to evaluate the external strengthening effect on TSPC strength.